Tissue Damage, Temperature, and pH Induced by Different Electrode Arrays on Potato Pieces (Solanum tuberosum L.) - González, Maraelys Morales; Aguilar, Claudia Hernández; Pacheco, Flavio Arturo Domínguez; Cabrales, Luis Enrique Bergues; Reyes, Juan Bory; Nava, Juan José Godina; Ambrosio, Paulo Eduardo; Domiguez, Dany Sanchez; Sierra González, Victoriano Gustavo; Pupo, Ana Elisa Bergues; Ciria, Héctor Manuel Camué; Alemán, Elizabeth Issac; et al. (Frontiers in Oncology, 2018)
One of the most challenging problems of electrochemical therapy is the design and selection of suitable electrode array for cancer. The aim is to determine how two-dimensional spatial patterns of tissue damage, temperature and pH induced in pieces of potato (Solanum tuberosum L., var. Mondial) depend on electrode array with circular, elliptical, parabolic and hyperbolic shape. The results show the similarity between the shapes of spatial patterns of tissue damage and electric field intensity, which, like temperature and pH take the same shape of electrode array. The adequate selection of suitable electrodes array requires an integrated analysis that involves, in a unified way, relevant information about the electrochemical process, which is essential to perform more efficiently way the therapeutic planning and the personalized therapy for patients with a cancerous tumor.